Implementation of the Problem Based Learning (PBL) Learning Model with the Assistance of Interactive Media to Improve Student Learning Outcomes in Indonesian Language Subjects in Grade 2 of SD Inpres Tulo - Safitri, Dian; Ulfah, Ulfah; Aqil, Muhammad; Lagandesa, Yun Ratna; Fasli, Muhammad (Journal of Educational Sciences, 2025)
The background of this study is the low reading comprehension and literacy skills of students as indicated by only 36.36% of students achieving the minimum completion criteria at the pre-action stage. This classroom action research aims to improve the learning outcomes of Indonesian language subjects of grade 2 students of SD Inpres Tulo through the application of the Problem Based Learning (PBL) model assisted by interactive media. Using classroom action research with data collection techniques using learning outcome tests, teacher and student activity observation sheets, and field notes. Quantitative descriptive analysis is used to calculate individual absorption and classical completion, while qualitative analysis is used to assess activity scores to assess the success of the actions taken. The results of the study showed a significant increase in student learning outcomes, with the average value increasing from 61.81 in the pre-action to 80.90 in cycle II and classical completion reaching 81.81%. Student activity also increased from the sufficient category to good. In conclusion, the use of PBL with relevant media can be an alternative strategy to improve literacy skills and can be adapted to other subjects at the elementary level.